2005
DOI: 10.1128/iai.73.8.4571-4580.2005
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of the Fungal Pathogen Candida albicans Requires the Five Isoforms of Protein Mannosyltransferases

Abstract: The PMT gene family in Candida albicans encodes five isoforms of protein mannosyltransferases (Pmt proteins Pmt1p, Pmt2p, Pmt4p, Pmt5p, and Pmt6p) that initiate O mannosylation of secretory proteins. We compared virulence characteristics of pmt mutants in two complex, three-dimensional models of localized candidiasis, using reconstituted human epithelium (RHE) and engineered human oral mucosa (EHOM); in addition, mutants were tested in a mouse model of hematogenously disseminated candidiasis (HDC). All pmt mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 38 publications
6
73
1
4
Order By: Relevance
“…Although additional Northern analysis revealed that PMT1 and PMT2 are also expressed under these conditions (data not shown), PMT2 was predicted to be essential based on studies of other microorganisms, and we also predicted that Pmt1 and Pmt2 likely function together as a heterodimer. In other fungi, Pmt4 enzymatic activity is important for cell wall formation, cell integrity, and pathogenesis but is not essential for viability (34,46). Therefore, for initial gene disruption experiments, we chose to study the PMT4 gene to assess the role of Pmt-mediated O mannosylation in C. neoformans growth and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although additional Northern analysis revealed that PMT1 and PMT2 are also expressed under these conditions (data not shown), PMT2 was predicted to be essential based on studies of other microorganisms, and we also predicted that Pmt1 and Pmt2 likely function together as a heterodimer. In other fungi, Pmt4 enzymatic activity is important for cell wall formation, cell integrity, and pathogenesis but is not essential for viability (34,46). Therefore, for initial gene disruption experiments, we chose to study the PMT4 gene to assess the role of Pmt-mediated O mannosylation in C. neoformans growth and pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…pmt4/pmt4 homozygous mutants are significantly attenuated in mouse models of hematogenously disseminated candidiasis (34). In our studies, we used two murine models of cryptococcal disease, intravenous and inhalation, to examine the role of Pmt4 in C. neoformans pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion of pmt4 is associated with a drastic reduction in appressorium formation and, more importantly, those appressoria that do form are nonfunctional in terms of plant penetration. Thus, protein O-mannosylation can now be considered a protein modification process essential for U. maydis virulence and, as PMT family proteins are not conserved in plants (Rouabhia et al, 2005;Bowman and Free, 2006), they may represent an interesting target for future antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Mannan synthesis is regulated by several specific glycosyl transferases. [15][16][17] It is also an immunochemical determinant of Candida spp. 18,19) It is of note that the structure of mannan is modulated by various culture conditions, such as temperature and pH.…”
Section: 6)mentioning
confidence: 99%